История становления санэпидслужбы на водном транспорте Днепровского бассейна - Коваль, А.А.; Пожар, А.И.; Матюк, А.Х.; Мироненко, У.П. (Актуальні проблеми транспортної медицини, 2005)
In the work presented they describe the sanitary-and-epidemiological service on the water transport of the Dnieper basin formation. They give a detailed chronology of the service development, examine the point of its reorganization. The authors express their opinion as to the present day decisions about the station mentioned above reorganization and the ways it is conducted.